Immunoglobulin M-degrading enzyme of Streptococcus suis (IdeSsuis) impairs porcine B cell signaling - Annika Katharina Breitfelder; Wieland Schrödl; Viktoria Rungelrath; Christoph Georg Baums; Gottfried Alber; Nicole Schütze; Uwe Müller (Frontiers in Immunology, 2023)
Streptococcus suis (S. suis) is an important porcine pathogen, causing severe disease like meningitis and septicemia primarily in piglets. Previous work showed that the IgM-degrading enzyme of S. suis (IdeSsuis) specifically cleaves soluble porcine IgM and is involved in complement evasion. The objective of this study was to investigate IdeSsuis cleavage of the IgM B cell receptor and subsequent changes in B cell receptor mediated signaling. Flow cytometry analysis revealed cleavage of the IgM B cell receptor by recombinant (r) IdeSsuis_homologue as well as IdeSsuis derived from culture supernatants of S. suis serotype 2 on porcine PBMCs and mandibular lymph node cells. Point-mutated rIdeSsuis_homologue_C195S did not cleave the IgM B cell receptor. After receptor cleavage by rIdeSsuis_homologue, it took at least 20 h for mandibular lymph node cells to restore the IgM B cell receptor to levels comparable to cells previously treated with rIdeSsuis_homologue_C195S. B cell receptor mediated signaling after specific stimulation via the F(ab’)2 portion was significantly inhibited by rIdeSsuis_homologue receptor cleavage in IgM+ B cells, but not in IgG+ B cells. Within IgM+ cells, CD21+ B2 cells and CD21- B1-like cells were equally impaired in their signaling capacity upon rIdeSsuis_homologue B cell receptor cleavage. In comparison, intracellular B cell receptor independent stimulation with tyrosine phosphatase inhibitor pervanadate increased signaling in all investigated B cell types. In conclusion, this study demonstrates IdeSsuis cleavage efficacy on the IgM B cell receptor and its consequences for B cell signaling.